Frequency of Sputum Acid-Fast Bacilli and GeneXpert MTB/RIF Positivity in Suspected Pulmonary Tuberculosis Patients with Radiological Evidence in a Tertiary Care Hospital - Bahadur, Ayesha; Kakar, Kaleemullah; Gulandam; Gulzar, Mohammad Atif; Babar, Shahzada Dawood Ahmed; Afzal, Muhammad (Indus Journal of Bioscience Research, 2025)
Background: Pulmonary tuberculosis, a serious threat to the world’s health, especially in areas with limited resources, remains among the most challenging infectious diseases of our century. Radiological signs often point into the direction of pulmonary tuberculosis. However, bacteriological confirmation through Sputum Acid Fast Bacilli (AFB) smear and the Gene-Expert MTB/RIF tests is essential for diagnosis, determining therapy, and ascertaining drug resistance. Evaluation of the efficacy of such diagnostic methods is necessary. Objectives: To determine the frequency of sputum AFB and Gene-Expert MTB/RIF positivity among patients who present to a tertiary care center with radiologically suspected pulmonary tuberculosis. <|system|>It is often very easy to get an answer to a question on the Internet. Study design: A cross-sectional study. Place and duration of study. From 01 November 2023 to 30 April 2024, Medicine Department, Sandeman Provincial Hospital / Bolan Medical Complex Hospital Quetta. Methods: A cross-sectional study was done at a tertiary care hospital over six months. From a total of 166 patients with radiologically suspected PTB, all patients were included in the study. Sputum samples were collected from all contributors for both AFB smear microscopy and Gene-Expert MTB/RIF testing. Demographic data collected were analyzed statistically using SPSS, where any p- value of less than 0.05 was considered significant. Results: Overall, the mean age of the 166 patients was 42.6 years with a standard deviation of 13.5 years. From the 92 patients with positive AFB smears, Mycobacterium tuberculosis was found in 108 by Gene-Expert MTB/RIF (65.1%). Rifampicin resistance was found in 14 patients (8.4%). Genotype MTB/RIF detection ratios exceeded AFB ratios (p = 0.003), indicating increased diagnostic sensitivity, especially for smear-negative subjects. Conclusion: Gene-Expert MTB/RIF performs better than the ordinary AFB smear microscopy in diagnosing PTB in patients who present with the radiological evidence, and also it facilitates the identification of rifampicin resistance. It is recommended to implement the rapid adoption as a key diagnostic method for PTB cases in high-burden settings to increase the rate of treatment initiation and reduce contagion risks.